Creative Climate and Organisational Resilience in the Banking Industry: The Mediating Role of Psychological Safety - Mumin, A.A. (University of Ghana, 2023)
The research investigated the relationship between creative climate and organisational resilience among Ghanaian-owned and Foreign-owned banks in the Greater Accra region, the capital of Ghana. The research further investigated the mediating role of psychological safety in the relationship between creative climate and organisational resilience. The study utilised a convenient sampling technique to sample 397 employees of Ghanaian-owned and Foreign-owned banks. 200 of the participants sampled were from Ghanaian-owned banks, and 197 were from Foreign-owned banks. The study deployed a quantitative cross-sectional design, where participants were administered questionnaires in softcopy and hardcopy to investigate creative climate, organisational resilience, and psychological safety. The study utilised structural equation modeling (Amos) to analyse the collected data. The analysed data revealed that the creative climate had a positive impact on the organisational resilience of Ghanaian-owned and Foreign-banks. Psychological safety was found to mediate the positive impact of the creative climate on the organisational resilience of banks in Ghana. Based on the outcome of the study, banks in Ghana were recommended to implement policies that allow employees to establish solid networks and relationships characterised by trust and support among them, promote collective learning, cooperation, and information exchange among members of the organisation, encourage managers in all roles and business divisions to openly discuss risks and risk management strategies with their staffs to help determine the direction and alignment of goals, skills, among others.
MPhil. Human Resource Management
Keywords: creative climate; organisational resilience; Ghana